Active Learning via Pair Quiz During COVID-19 Pandemics for Engineering Students - Abdul Karim, S.A. (Springer Science and Business Media Deutschland GmbH, 2022)
Due to novel coronavirus (COVID-19), higher learning institutions and schools have opted the online based learning instead of face to face (F2F) for their teaching and learning (T&L) activities. Universiti Teknologi PETRONAS (UTP) also has no exception to this matter. Beginning May 2020 semester, all T&L in UTP are implemented through online platform such as BigBlueButton (BBB) and Microsoft Team (MS Team). BBB is running on ULearn platform, while MS Team is running via Microsoft team. Active learning (AL) approach have been fully utilized for T&L deliveries. One of the AL techniques is the implementation of pair- quiz as one of assessment method for Statistics and Application subject. Pair-quiz can be considered as novelty in T&L implementation especially during COVID-19 pandemic. From the study, pair-quiz provides better option to the students in securing higher course work marks while improving their understanding on the subject matter. Furthermore, through pair-quiz, the students have become peer helpers to each other. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.